# Simple question...yet oh so hard for me. TT__TT

by .hacker//Kazu
Tags: questionyet, simple, tttt
$$-3^{4}+(-3)^{3}-(-3)^{2}$$ i think this is what you meant, because your notation is a little ambiguous. then if this is the case we have
$$-3^{4}+(-3)^{3}-(-3)^{2}=-81-27-9=-117$$ well there are two mistakes on what you did, first $$-3^{4}=-81$$ and not 81, pay heed, the minus sign is not included whithin the power, so the power does not actually affect the sign here, also $$-(-3)^{2}=-9$$ be carefull again the first minus sign is not included within the power, so the power of two only affects(changes) the second minus sign that is included whithin the bracktets. I hope this helps!
 P: 1,633 Simple question...yet oh so hard for me. TT__TT here are a couple of examples i will write down for you $$-2^{4}=-16$$ wheras $$(-2)^{4}=16$$ $$(-3)^{2}=9$$ $$(-3)^{3}=-27$$ you see that odd powers do not affect the sign even if the sign is included within the brackets. $$-(-4)^{2}=-16$$ wheras $$-(-4)^{3}=64$$